Increase nitric oxide synthase activity in parotid glands from rats with experimental periodontitis - Miozza, V. (2010)
OBJECTIVE: In this study we investigated the activity of the nitric oxide synthase (NOS) in parotid glands from rats with experimental periodontitis and controls. METHODS: Periodontitis was produced by a ligature placed around the cervix of the two lower first molar. Experiments were carried out 22 days after the ligature. RESULTS: Ligation caused an increase in parotid NOS activity. The selective blocker of the inducible isoform of the enzyme partially inhibited its activity in parotid glands from rat with ligature. In controls, the activity was partially inhibited by the antagonists of the selective neural and endothelial isoforms. NOS activity in rats with ligature was cyclic adenosine monophosphate (cAMP)-dependent while in controls it was calcium-dependent. Prostaglandin E₂ concentration was increased in parotid gland from rats with ligature. The inhibitor of prostaglandin production, FR 122047, diminished both, prostaglandin production and NOS activity. In rats with ligature unstimulated amylase released is increased. Both, prostaglandin and NOS were involved in the increment of amylase release. CONCLUSION: It can be concluded that in parotid glands from ligated rats, prostaglandin E₂ production is increased and, through cAMP accumulation, activates the inducible NOS isoform. The increment of nitric oxide production participates in the increase in basal amylase release.